2014
DOI: 10.1159/000360376
|View full text |Cite
|
Sign up to set email alerts
|

The Pellicle and Erosion

Abstract: All tooth surfaces exposed to the oral environment are naturally coated by the acquired salivary pellicle. The pellicle is composed of adsorbed macromolecular components from saliva, gingival crevicular fluid, blood, bacteria, mucosa and diet. The pellicle (formed in situ/in vivo) functions as a semipermeable network of adsorbed salivary macromolecules and provides partial protection against acidic challenges; however, it cannot completely prevent demineralization of the tooth surface. The physiological pellic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
120
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 48 publications
4
120
0
17
Order By: Relevance
“…As previously established in the literature, saliva plays an important role in reducing erosive tooth wear before an erosive/abrasive attack [Amaechi and Higham, 2001] due to the formation of the salivary pellicle [Hannig, 2002;Hara et al, 2006]. The salivary pellicle has been described as a semipermeable membrane rich in proteins with acid-protective properties [Hannig and Hannig, 2014]. In the present study, after the formation of the salivary pellicle, the appliance was kept out of the mouth for 1 h, and this may have modified some of its proteins.…”
Section: Discussionsupporting
confidence: 51%
“…As previously established in the literature, saliva plays an important role in reducing erosive tooth wear before an erosive/abrasive attack [Amaechi and Higham, 2001] due to the formation of the salivary pellicle [Hannig, 2002;Hara et al, 2006]. The salivary pellicle has been described as a semipermeable membrane rich in proteins with acid-protective properties [Hannig and Hannig, 2014]. In the present study, after the formation of the salivary pellicle, the appliance was kept out of the mouth for 1 h, and this may have modified some of its proteins.…”
Section: Discussionsupporting
confidence: 51%
“…The acquired pellicle has been shown to have properties that may protect the enamel against mild erosive challenges in situ [Hara et al, 2006]. However, a recent review concluded that only limited scientific data is available regarding the protective properties of the pellicle against dental erosion [Hannig and Hannig, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the buffering effects of saliva and the clearance of acids in the oral cavity, the interactions at the tooth surface have to be considered, especially the omnipresent pellicle [Hannig and Hannig, 2014]. This physiological coating is formed almost instantaneously on all solid substrata in the oral cavity.…”
mentioning
confidence: 99%
“…The pellicle layer contains many protective and antibacterial components and serves as a lubricant [Hannig and Joiner, 2006]. Furthermore, it acts as a barrier against erosive noxae, but is semipermeable and, therefore, its protective effect is limited [Hannig et al, 2007[Hannig et al, , 2009a[Hannig et al, , 2012Hannig and Hannig, 2014]. Pellicle formation is of high selectivity, and the sustainable immobilization of protective ions and molecules at the tooth surface is rather difficult [Hannig and Joiner, 2006].…”
mentioning
confidence: 99%